Effect of Acid Medium on Lead-Steel Couple - K. Gomma, Gamal (Asian Journal of Chemistry, 2010)
The effects of oxalic acid and perchloric acid have been studied on the Pb-Fe couple by means of the open circuit potential and the galvanic current of the couple electrodes. The potential of the coupled as well as galvanic current were followed as a function of time till the steady state was attained. In all cases of oxalic acid and perchloric acid in the pH range 1.5–6.5, lead is the more noble electrode of the couple. This is due to the weak complexing of lead in these solutions. Lead is initially anodic to steel. However, reversal of polarity takes place after some time and steel becomes the anode of the couple.